Managing screening and diagnosis of Zika in the Emergency Department. Issue 2 (March 2017) - de Tantillo, Lila; Gonzalez, Juan M.; Ortega, Johis
Zika has emerged as a rapidly spreading infection worldwide. Clinicians in many parts of the world must be prepared to screen for symptoms and diagnose patients with this disease. In particular, pregnant women who may have experienced exposure to Zika must be treated with care and sensitivity due to serious risk for pregnancy complications among those who contract the infection. In response to the outbreak, patient management guidelines have been established for all who may be symptomatic or potentially at risk of infection with Zika. Clinicians globally can prepare to implement such protocols to help contain this disease.